Optofluidic devices with programmable and responsive functions - Wang, Chenlu (Nanyang Technological University, 2022)
Optofluidics, which takes the advantage of optics and microfluidic integration, has attracted extensive attention for its high reconfigurability and integration capability in many photonic applications. Optofluidic devices provide a promising platform by exploiting the interaction between microfluid and light at the microscale to create highly versatile systems, including but not limited to sensing, lighting, and communication. This thesis aims to develop optofluidic devices with responsive and programmable functions under different configurations. In the former part of the thesis, we demonstrated highly versatile functions of fiber-based optofluidic devices through unique design and control of infiltration patterns and resonator structures. Specific functions include enhanced sensing application, multicolor laser source, and information security system. In the latter part of the thesis, inkjet-printed optofluidic devices were developed for anticounterfeiting and optical encryption. Firstly, a highly responsive temperature optofluidic sensor was designed and fabricated by selectively infiltrating the proposed liquid into a dual-core photonic crystal fiber. By introducing liquid into the central airhole of photonic crystal fiber, the high-temperature-dependent central liquid core will modulate the directional coupling between two solid cores, and thus the temperature sensitivity is enhanced with a stronger light-matter interaction. Electrical field and optical mode distributions at different temperatures were numerically simulated, which were in good agreement with the experimental results. Secondly, a programmable full-color optofluidic laser was developed by infiltrating multicolored photonic microdroplets inside of the fiber. Dye-doped cholesteric liquid crystal droplets were introduced as microcavities, which support whispering gallery mode lasing emissions. Besides, a novel approach for tuning lasing wavelengths over a broad range was demonstrated by manipulating the topological structure of cholesteric liquid crystal droplets. Laser emission wavelengths covering the entire visible spectrum were acquired by four distinct dye-doped liquid crystal droplets representing red, green, blue, and yellow. By infiltrating different combinations of different microlasers into the optical fiber, a programmable full-color optofluidic fiber laser was achieved. Thirdly, an anticounterfeiting system by multicolor light mixing in optofluidic concave interfaces was created. By encapsulating dye-doped photonic resonators into a concave skydome structure, an iridescent ring pattern was generated at the edge of the hemisphere as a security label due to multicolor light reflection and mixing at optofluidic concave interfaces. Infinite coding capacity was achieved by considering the features of the encapsulated microresonators, including cavity sizes, color combinations, and spatial locations. An artificial intelligence based machine vision system was built for authentication. Finally, by combining spatial and spectral characteristics of photonic resonators, a multilevel optical security system was developed for optical information. Multiplexed fingerprints with unclonable anticounterfeiting features were obtained, including photoluminescence security patterns, photonic barcodes, and CIE color coordinators. Enhanced coding capacity was achieved by introducing different combinations of dye-doped photonic resonators. The proposed strategy could be widely applied to various platforms and anticounterfeiting systems. The overall results and investigations presented in the thesis may provide inspiration for the development of responsive and programmable optofluidic photonic devices.